2018
DOI: 10.1016/j.omtn.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 Suppresses miR-3178 to Promote the Metastasis Invasion Cascade via Upregulation of TRIOBP

Abstract: Specificity protein (Sp1) plays an important role in invasion-metastasis cascade. Sp1 regulation on protein coding genes has been extensively investigated; however, little is known about its regulation on protein non-coding genes. In this study, miR-3178 is reported as a novel target of Sp1 in multiple cancer cell models. Sp1 functions as its transcriptional suppressor as evidenced by luciferase reporter and chromatin immunoprecipitation (ChIP) assays. In line with the pro-metastatic role of Sp1, miR-3178 exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Here, we intended to explore the biologic role of circ_0000520 in cell growth and metastasis of BCa, and to figure out the interaction of circ_0000520 , miR-1296 and specificity protein 1 (SP1), a basal transcriptional factor that widely regulates genes to contribute to the hallmarks of cancers including BCa. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Here, we intended to explore the biologic role of circ_0000520 in cell growth and metastasis of BCa, and to figure out the interaction of circ_0000520 , miR-1296 and specificity protein 1 (SP1), a basal transcriptional factor that widely regulates genes to contribute to the hallmarks of cancers including BCa. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PC3-5 V, PC3–57, and PC3–29 are clonal cell lines derived from PC3. Discrepant results between PC3–57 + CD82 and PC3–29 + CD82 clonal cells when compared with PC3-5 V -CD82 cells may be due to the fact that prostate tumor can harbor multiple genetically distinct cancer clones with heterogenous ERG+, ETS+, SPI+ and triple negative subtypes [ 80 , 81 ] that can affect different gene regulation and pathways. Moreover, high vs. low metastatic cells have been known to be derived from parental PC3 cells [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests an interesting interaction between SP1 and micro-RNAs. In the study of prostate cancer, it was found that SP1 regulates the expression of miR-3178 and affects the metastasis of prostate cancer cells [18]. In esophageal squamous cell carcinoma, SP1 directly activates the expression of miR-205 to regulate the radiation sensitivity of cancer cells [19].…”
Section: Introductionmentioning
confidence: 99%